APLIKASI TEKNOLOGI AUGMENTED REALITY DALAM KONSERVASI SITUS WARISAN BUDAYA DAN MITIGASI BENCANA GUNUNG GALUNGGUNG JAWA BARAT INDONESIA - wanda listiani; Sri Rustiyanti; Fani Dila Sari; IBG. Surya Peradantha (LPPM Universitas PGRI Adi Buana Surabaya, 2021)
The name Galunggung is very well known to the people of Indonesia as the name of the mountain and the name of an Old Sundanese Manuscript. The ancient manuscript of Amanat Galunggung is a manuscript written in the 16th century and contains the teachings of life or local genius of the Sukapura or Tasikmalaya people. Mount Galunggung has experienced several eruptions from 1822 to 1983. The eruption of Mount Galunggung has had a catastrophic impact on the community and provided long term benefits for improving the soil fertility around the Mount Galunggung site such as the Indihiang site. Various disasters that have occurred due to volcanic eruptions in various regions have become a source of learning for the community to mitigate disasters from an early age. This research uses qualitative methods and digital augmented reality techniques. Augmented Reality can be used in visualizing and simulating mountain sites or other cultural heritage sites. The results of this study recommend the application of Augmented Realty technology in the conservation of cultural heritage sites and disaster mitigation as well as the planning program for the nomination of mountain sites in Indonesia for UNESCO’s world cultural heritage by the Indonesian government. Various efforts to develop site conservation with digital 4.0 technology and assistance for local communities involving universities, local governments, museum communities and the cultural arts tourism industry. The use of Augmented Reality can be useful for increasing understanding and learning experiences about cultural sites and heritage in tertiary, primary and secondary education.